Relationship between Exposure to COVID-19 and Hemoglobin Levels in Pregnant Women - Dwi Ernawati; Yuni Kusmiyati; Atik Ismiyati; Jinli Song; Qurry Amanda Izhati (Universitas Ahmad Dahlan, 2023)
Background: Mothers who are exposed to COVID-19 have an impact on decreasing HB levels causing anemia thereby increasing the risk of morbidity and mortality in mothers during childbirth. Purpose: To determine the relationship between exposure to COVID-19 during pregnancy and hemoglobin levels in the Bantul II Health Center area. Methods: This study is a quantitative study with a retrospective cohort study design. The sample in this study was 26 pregnant women in each group (exposed and not exposed to COVID-19), selected based on inclusion criteria with simple random sampling. This research was conducted in the Bantul II Health Center area from October 2021 – February 2022. Data was collected by measuring Hb levels and filling out questionnaires. Data were analyzed by independent t-test and correlation. Results: There was no difference in the average Hb level in pregnant women who were exposed and not exposed to COVID-19 (Mean difference = 0.785; 95% CI = -0.164-1.734; p=0.103). Meanwhile, for the external variables, namely age (p=0.839), parity (p=0.565), nutritional status (p=0.233), and consuming Fe tablets (p=0.286) in the case group, age variable (p=0.492), parity (p=0.34), nutritional status (p=0.511) in the control group was not associated with a decrease in Hb levels. The variable consuming Fe tablets (p=0.049) in the control group was associated with a decrease in Hb levels. Conclusion: Pregnant women experience a decrease in Hb levels not due to exposure to COVID-19. Age, parity, nutritional status, and consumption of Fe tablets had no relationship with the decrease in Hb levels.